Manufacturing Mammies: The Burdens of Service Work and Welfare Reform among Battered Black Women - Davis, Dana-Ain (Anthropologica, 2022)
The impact of economic restructuring from industry to service that began in the 1970s continues to leak across cities in the United States. One outcome of restructuring has been the targeted focus of corporate interests in realizing profits. To that end, corporations have become increasingly engaged in policy issues, specifically decreased wages and deregulation. The confluence of economic restructuring, corporate interests and neo-liberal policy have converged at the lived experience of battered Black women on welfare. This paper examines the links between these broader processes that have influenced welfare reform policy, battered Black women and historically constructed images of Black women.